Design of a Copy Service E-Marketplace Android-Based in the Parongpong District - Lahallo, Stefhanie Ancela; Aritonang, Raja Daud (Pandawan, 2020)
Technology has an important role in the progress of doing business. Lately, the Indonesian e-marketplace industry is indeed very developed. They help Indonesian people to shop with just one click at their own home. The e-marketplace is a virtual online market platform where companies can register as buyers and sellers to conduct business to business transactions over the Internet. The use of the Internet has helped remove intermediaries in a transaction. The purpose of this study is to assist copy service owners in conducting conventional business activities to be digital business activities. And make it easier for customers to find a copy service in Parongpong District. This study uses 2 research methods, field surveys and literature studies. Researchers intend that the e-marketplace copy service android-based system will be used by owners of copy services to promote their services and is also expected to be used by consumers to order copy services.